Women's decision making regarding prenatal screening for fetal aneuploidy: A qualitative comparison between 2003 and 2016. (September 2018) - van Bruggen, Metje J.; Henneman, Lidewij; Timmermans, Daniëlle R.M.
Highlights: Most Dutch women who want to be informed about prenatal screening are counselled by midwives. Dutch pregnant women's decision making in prenatal screening has not essentially changed over the years. New screening possibilities do not seem to impact women's deliberated decision process. Costs and media attention about prenatal screening and Down syndrome may impact women's free decision making. Precautions should be taken to ensure informed and deliberate decision making. Abstract: Objective: Situational factors of prenatal screening have changed in recent decades. To explore the effect of a changing context on women's decision making, differences and similarities in the decision-making process of pregnant women regarding prenatal screening for fetal aneuploidy between two periods in time were studied. Design: A qualitative comparison was made between a dataset of 22 semi-structured interviews with pregnant women from 2003 and a newly collected dataset with 19 semi-structured interviews from 2016. Findings: Overall, women reported similar considerations in their decision-making process in 2003 and 2016, suggesting that decision making has not essentially changed. In 2016, women were still making a deliberate decision, however for some women costs and societal views as to what is acceptable did appear to impact the decision-making process . Moreover, new screening possibilities (e.g. improved test characteristics and including more conditions to be screened) seemed to impact the decision outcome . Conclusions: Since most women based their decisions mainly on their personal values and personal experiences rather than on situational factors, the results suggest that the changing context with regard to prenatal screening had no major effect on women's decision making. It therefore seems unlikely that future changes in the field of prenatal screening will drastically change the decision-making process of pregnant women as long as informed and deliberate decision making is safeguarded.